2023
DOI: 10.3390/ijms241914815
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epithelial to Mesenchymal Transition in Colorectal Cancer

Jian Lu,
Marko Kornmann,
Benno Traub

Abstract: The epithelial–mesenchymal transition (EMT) is a cellular reprogramming process that occurs during embryonic development and adult tissue homeostasis. This process involves epithelial cells acquiring a mesenchymal phenotype. Through EMT, cancer cells acquire properties associated with a more aggressive phenotype. EMT and its opposite, mesenchymal–epithelial transition (MET), have been described in more tumors over the past ten years, including colorectal cancer (CRC). When EMT is activated, the expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 133 publications
0
11
0
Order By: Relevance
“…These results indicated that TGF-β play important role in RCC and promote the EMT in CSCs, which related with recurrence and metastasis. Accumulating evidences have shown the connection between the EMT and CSCs in human cancers, and TGF-β plays pivotal role not only in the stemness of CSCs but also in the immune cells in tumor microenvironment [24][25][26]. TGF-β can control adaptive immunity by promoting the expansion of Treg cells directly, regulating the regulatory CD4 + T cell response, controlling the function of effector T cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that TGF-β play important role in RCC and promote the EMT in CSCs, which related with recurrence and metastasis. Accumulating evidences have shown the connection between the EMT and CSCs in human cancers, and TGF-β plays pivotal role not only in the stemness of CSCs but also in the immune cells in tumor microenvironment [24][25][26]. TGF-β can control adaptive immunity by promoting the expansion of Treg cells directly, regulating the regulatory CD4 + T cell response, controlling the function of effector T cells.…”
Section: Discussionmentioning
confidence: 99%
“…During progression, cancer cells acquire a phenotypic change from epithelial to mesenchymal and exhibit aggressive behavior. This phenomenon, the so-called EMT, plays a critical role in cancer progression, metastasis, and recurrence after curative treatment for primary lesions [21,22] . Our in vitro data demonstrate that BAP1 promotes cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of celecoxib (a selective COX-2 inhibitor) as an adjuvant to chemotherapy significantly improved the overall survival and disease-free survival in COX-2-positive gastric cancer patients [128], and its oral administration significantly improved responses in patients with recurrent ovarian cancer characterized by platinum-based drug resistance (phase II, NCT01124435) [129]. Another COX-2 inhibitor, rofecoxib, in combination with cyclophosphamide and vinblastine, showed a 30% clinical benefit in patients with advanced solid tumors [130], and low-dose aspirin prevented colorectal cancer in patients with familial adenomatous polyposis by suppressing the recurrence of colorectal polyps (UMIN000018736) [131], a process associated with EMT [132]. These results are consistent with the recent retrospective analysis by Cai et al demonstrating that the use of non-steroidal anti-inflammatory drugs during radical resection in NSCLC patients correlates with outcomes [133].…”
Section: Clinical Trials Of Drugs Targeting Key Regulators Of Inflamm...mentioning
confidence: 99%